Prevalence of hypertension in a rural community of North Kerala, India: a cross sectional study - B. C., Satheesh; C., Mohammad Iliyas (International Journal Of Community Medicine And Public Health, 2017)
Background: Hypertension is major risk factor for CVDs and its complications account for 9.4 million deaths worldwide every year. Hypertension itself is responsible for about 45% and 51% deaths due to heart disease and stroke respectively. Hypertension is a major public health concern in India both in urban and rural areas and it is increasing at an alarming rate in rural population. Because of inadequate access to health care facilities at rural areas, the early screening and treatment of hypertension is not done regularly, so we conducted this study. Objectives: To determine the prevalence of hypertension in a rural community of North Kerala. Methods:A community based cross sectional study was conducted at rural field practice area of Kannur Medical College, Kannur. Sample size was 151 and convenient sampling method used. Data was collected visiting homes and blood pressure measured with mercury sphygmomanometer by. Descriptive statistics were used to analyse the data. Results: Among 152 participants, 52.3% and 47.7% were females and males respectively and mean age of the participants was 51.01±15.25 years. The overall prevalence of hypertension among them was 18.5% and the proportion of hypertension was more among the age group of 60-69 years (39.3%). Conclusions:Our study shows that hypertension is not only a concern of the urban population, but also important issue in rural areas. Newly diagnosed cases are more which indicates, people are not aware about importance of regular screening. Since screening helps in early detection, so strengthening of health facilities and creation of awareness at rural levels will reduce the morbidity and mortality due to hypertension and its complications.